2014
DOI: 10.1038/ncomms6348
|View full text |Cite
|
Sign up to set email alerts
|

A short acidic motif in ARF guards against mitochondrial dysfunction and melanoma susceptibility

Abstract: ARF is a small, highly basic protein that can be induced by oncogenic stimuli and exerts growth-inhibitory and tumour-suppressive activities through the activation of p53. Here we show that, in human melanocytes, ARF is cytoplasmic, constitutively expressed, and required for maintaining low steady-state levels of superoxide under conditions of mitochondrial dysfunction. This mitochondrial activity of ARF is independent of its known autophagic and p53-dependent functions, and involves the evolutionarily conserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…It has to be underlined that ARF region 100–132, required for both pFAK activation and survival, has an established role in autophagy as reported in Budina-Kolomets et al 36 thus suggesting that ARF ability to regulate autophagy could be involved in this mechanism and it is independent from the reported ARF functions in mitochondrial homeostasis. 25 However, from experiments performed with mitotracker staining, we cannot exclude that ARF localization to cell periphery during the early phases of cell spreading (data not shown) could be in part mediated or primed by mitochondria accumulation to sites of actin remodeling.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It has to be underlined that ARF region 100–132, required for both pFAK activation and survival, has an established role in autophagy as reported in Budina-Kolomets et al 36 thus suggesting that ARF ability to regulate autophagy could be involved in this mechanism and it is independent from the reported ARF functions in mitochondrial homeostasis. 25 However, from experiments performed with mitotracker staining, we cannot exclude that ARF localization to cell periphery during the early phases of cell spreading (data not shown) could be in part mediated or primed by mitochondria accumulation to sites of actin remodeling.…”
Section: Discussionmentioning
confidence: 93%
“…Finally, we tested different ARF point mutants derived from melanoma predisposing mutations 25 affecting single residues within an acidic motif (65–70 aa). We found that all of them are still able to induce pFAK stabilization, at efficiency similar or higher than the wt protein ( Supplementary Figure S7 ).…”
Section: Resultsmentioning
confidence: 99%
“…A missense mutation in p14 (c.62G>A, p.(R21K), exon 1β) was identified in an individual affected with CM aged 54 years and no family history of CM. To-date, no melanoma families have been identified that carry missense mutations in exon 1β, however, very recent studies have shown that p14-specific alterations in CDKN2A exon 2 impair the ability of p14 to control superoxide levels and suppress growth of melanoma cells in vivo [ 43 ]. Previously, only whole gene deletions, insertions or splice-site mutations in p14, have been determined as pathogenetic [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Reef et al [ 62 ] found that Arf can localize to mitochondria to regulate autophagy and apoptosis. More recently, Christensen et al [ 63 ] reported that Arf controls superoxide production by translocating to mitochondria in pre-senescent cells and binding to Bcl-xL. Arf-deficient cells also demonstrated enhanced respiratory capacity, but since the cells used in these experiments were also deficient in p16 it is not clear to what extent the effects on mitochondrial function could be attributed to Arf vs .…”
Section: Discussionmentioning
confidence: 96%
“…Arf-deficient cells also demonstrated enhanced respiratory capacity, but since the cells used in these experiments were also deficient in p16 it is not clear to what extent the effects on mitochondrial function could be attributed to Arf vs . p16 [ 63 ]. By contrast, we have not found p16 to be localized in the mitochondria in unstressed fibroblasts (B. Liu and Grossman, unpublished observations), and noted decreased mitochondrial respiration and abnormal mitochondrial structure in the cells used here which were deficient in p16 but not Arf.…”
Section: Discussionmentioning
confidence: 99%